The application of the modular multilevel matrix converter in high-power wind turbines - Diaz, Matias; Espinoza, Mauricio; Mora, Andreas; Cardenas, Roberto; Wheeler, Patrick (2016)
The trend in wind turbines has shown an ongoing power rating growth, reaching sizes up to 10 MW. Multilevel converters have therefore become a favourable solution for Multi-MW Wind Energy Conversion Systems (WECSs), due to high efficiency, reliability, controllability and the ability to reach high power/voltage ratings. Moreover, stringent grid codes to regulate the connection of WECSs to the electrical networks have been developed in countries with a high penetration of wind energy. In this context, this paper introduces the novel application of the Modular Multilevel Matrix Converter for interfacing Multi-MW Wind Turbines to provide decoupled input-output regulation, variable speed operation and fulfilment of modern grid codes.